2008
DOI: 10.1163/156854108785787271
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory studies on the biocontrol potential of the predatory nematode Koerneria sudhausi (Nematoda: Diplogastridae)

Abstract: The predatory nematode Koerneria sudhausi reproduced on bacteria that developed spontaneously on a nutrient medium in Petri dishes. The nematode population had a female/male ratio of 2.9 : 1, but female nematodes could reproduce asexually on the bacteria. Each female produced about 60 progeny at 25 • C in 9 days without mating. The generation time (egg to egg) at the same temperature was 8 days. Koerneria sudhausi reproduced at 17 • C at the same rate as at 25 • C, if the bacteria were available as a food sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The following nematodes and laboratory strains were used in this study: C. elegans N2 ( C. elegans Genetics Center); P. pacificus PS312 ( Sommer et al 1996 ), A. sudhausi SB413 ( Bar-Eyal et al 2008 ; Fürst von Lieven 2008 ), and A. seani RS1982 ( Kanzaki et al 2015 ). Note that A. sudhausi was originally described as Koerneria sudhausi .…”
Section: Methodsmentioning
confidence: 99%
“…The following nematodes and laboratory strains were used in this study: C. elegans N2 ( C. elegans Genetics Center); P. pacificus PS312 ( Sommer et al 1996 ), A. sudhausi SB413 ( Bar-Eyal et al 2008 ; Fürst von Lieven 2008 ), and A. seani RS1982 ( Kanzaki et al 2015 ). Note that A. sudhausi was originally described as Koerneria sudhausi .…”
Section: Methodsmentioning
confidence: 99%
“…Osman (1988), in a pot experiment, found that by adding predatory nematode, Diplogaster sp., the parasitic population of Tylenchulus semipenetrans or M. javanica in the roots of sour orange and tomato, respectively, were significantly reduced. Diplogasterid predator, Koerneria sudhausi cultured on bacteria, resulted in a reduced tomato root galling index when the predator was introduced into the M. javanica-infested soil in pots (Bar-Eyal et al 2008).…”
Section: Pot Studymentioning
confidence: 99%